2011
DOI: 10.5751/es-04075-160306
|View full text |Cite
|
Sign up to set email alerts
|

Economic Behavior in the Face of Resource Variability and Uncertainty

Abstract: ABSTRACT. Policy design is largely informed by the traditional economic viewpoint that humans behave rationally in the pursuit of their own economic welfare, with little consideration of other regarding behavior or reciprocal altruism. New paradigms of economic behavior theory are emerging that build an empirical basis for understanding how humans respond to specific contexts. Our interest is in the role of human relationships in managing natural resources (forage and livestock) in semiarid systems, where spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(37 reference statements)
1
17
1
Order By: Relevance
“…While some recent studies demonstrated that resource scarcity or unpredictability (e.g. in relation to climate change) can enhance conflicts and violence among humans (Le Billon 2001;Hsiang et al 2013), other, less prominent studies point out that resource variability can also promote cooperation (Bogale and Korf 2007;McAllister et al 2011). An interesting example on the emergence of cooperation examined local versus large-scale social conflicts originating from heterogeneity in wealth and resources (Abou Chakra and Traulsen 2014).…”
Section: A Driver Of Cooperationmentioning
confidence: 99%
“…While some recent studies demonstrated that resource scarcity or unpredictability (e.g. in relation to climate change) can enhance conflicts and violence among humans (Le Billon 2001;Hsiang et al 2013), other, less prominent studies point out that resource variability can also promote cooperation (Bogale and Korf 2007;McAllister et al 2011). An interesting example on the emergence of cooperation examined local versus large-scale social conflicts originating from heterogeneity in wealth and resources (Abou Chakra and Traulsen 2014).…”
Section: A Driver Of Cooperationmentioning
confidence: 99%
“…In other words, 0.41 United States dollar must be consumed when 1 United States dollar was produced under perfect competition. It was thus clear that the parameter was a measure for the prospect of capital economic analysis and of venture forecasting [20][21][22][23].…”
Section: Resource Efficiency For Utilization In a Spraying Reactormentioning
confidence: 99%
“…Finally, certain concepts from having only a single developed technology are referenced to optimize the coal resource allocation. Suppose that the utilization options only include the above four routes for the coal under perfect competition conditions [30]. In this situation, the best utilization of resources needs to be determined.…”
Section: A Number Of Options For Developed Technologymentioning
confidence: 99%